THE EFFECT OF ASSEMBLR EDU APPLICATION ON STUDENTS’ VOCABULARY MASTERY (QUASI-EXPERIMENTAL STUDY AT THE EIGHTH GRADE OF JUNIOR HIGH SCHOOL 20, BENGKULU CITY, ACADEMIC YEAR 2025–2026) - Amelia, Yosa; Nadrah; Haryanto, Endang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Vocabulary mastery is an essential component of English learning because it supports students’ reading, writing, speaking, and listening skills. However, many students still have limited vocabulary mastery due to the use of conventional teaching methods that rely on memorization and translation. Therefore, innovative learning media are needed to enhance students’ vocabulary learning. This study aims to determine the effect of using the Assemblr Edu app on the vocabulary mastery of Eighth Grade of Junior High School 20, Bengkulu City during the 2025–2026 school year. This study employed a quantitative approach with a quasi-experimental non-equivalent control group design. The research sample was selected using purposive sampling and consisted of an experimental class and a control class. Data were collected through vocabulary tests pretest and posttest. The experimental class received instruction using the Augmented Reality (AR)-based Assemblr Edu app, while the control class received conventional instruction using printed picture media. The data were analyzed using an independent samples t-test with SPSS version 27. The results show a significance value (Sig., 2-tailed) of 0.003, which is less than 0.05 (0.003 < 0.05). Thus, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. It can be concluded that the Assemblr Edu app is effective in improving students’ vocabulary mastery and can serve as an alternative learning medium in English language instruction.